Effect of temperature on the wear behavior of NiTi shape memory alloy - Yan, Lina (2015)
This article aims to provide a fundamental understanding of the deformation mechanisms of NiTi shape memory alloy (SMA) during the wear process at different temperatures when different microstructures are present. Three temperature regimes were selected namely, T < Mf, As < T < Af, and T > Af, where fully martensitic, martensite co-existing with austenite, and fully austenitic microstructures were formed, respectively. When T < Mf, it was observed that the coefficient of friction had decreased initially and thereafter stabilized at a lower value with increasing wear cycles. More decrease was found when the temperature was near to As. Furthermore, when tested above Af, the coefficient of friction had decreased more significantly under higher load. Difference in the trend of coefficient of friction at different temperatures is originated from the different deformation mechanisms involved in the wear process, particularly the martensite detwinning process, the stress-induced phase transformation process, and the plastic deformation of martensite.